PENGARUH BIMBINGAN BELAJAR TERHADAP PEMAHAMAN GAYA BELAJAR SISWA - Theodora Astrinia Putri Wirandini; Umbu Tagela; Yustinus Windrawanto (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
This study aims to determine the effect of tutoring on understanding the learning styles of class XII students at SMK PGRI 2 Salatiga. This type of research is causal comparative research. In this study, the population was 84 students of class XII at SMK PGRI 2 Salatiga and the sample was taken using total sampling technique. Data collection in this study was revealed using a closed questionnaire instrument and the research data were analyzed using a simple linear regression technique with the help of the IBM SPSS Statistics 25.0 program. The results of this study indicate that there is a significant effect of tutoring on understanding the learning styles of class XII students at SMK PGRI 2 Salatiga. These results are proven by obtaining tcount > ttable (10.870 > 1.987) and a probability value (p) of (0.000 <0.05)